Penerapan Model Pemblajaran Make a Match Untuk Meningkatkan Hasil Belajar Muatan Matematika Siswa Kelas II Semester I SD Negeri 1 Pertima - I Gusti Ayu Lilis Astuti (Jayapangus Press, 2019)
This research is motivated by the low mathematics learning outcomes of the second semester students in the first semester at SDN 1 Pertima. Based on the results of preliminary observations, it was obtained that the absorption capacity of grade 1 students at SD Negeri 1 Pertima only reached 60%. Teaching improvement in mathematics learning outcomes for students in grade II of first semester of SD Negeri 1 in the academic year 2017/2018 after applying the learning model to make a match This type of research is Classroom Action Research. Place of action in SD Negeri 1 Pertima by taking the research subjects of the second semester students in the first semester who took 13 students. The object of this research is the learning outcomes of mathematics students in the second semester of semester I on theme 2, namely the multiplication material and the division of chopped numbers with a product of up to 100. The collection of this data using the collection method to study student learning and test methods to produce student learning outcomes after data collected, then analyzed using descriptive statistical methods. The application of learning models makes the match can improve mathematics learning outcomes of students in grade II of SD Negeri 1 Pertima in the 2017/2018 Learning Year. The average student mathematics learning outcomes in the first cycle is 66 with a classical completeness of 54%, in the second cycle increased to 76 with a classical completeness of 92%, this has been proven to improve mathematics learning outcomes by 38%.